Comparison of Diesel Engine Characteristic Using Pure Coconut Oil, Pure Palm Oil, and Pure Jatropha Oil as Fuel - Iman K. Reksowardojo; Y. Hartanto; T. P. Brodjonegoro; W. Arismunandar (Jurnal Teknik Mesin (Sinta 3), 2009)
Diesel engine can be operated on either pure plant oil (PPO) oil or biodiesel. Biodiesel production process is expensive due to many stages of processes, while PPO has a lower cost of production, lower energy consumption, and simpler process. There are several potential biofuel resources in Indonesia such as coconut, palm, and jatropha. They are tropical plants with large amonts of their quantity. Experiment was conducted in 17 hours engine running test (endurance test) with various operating cycle conditions. Test fuels are pure coconut oil (PCO), pure palm oil (PPaO), pure jatropha oil (PJO), and diesel fuel (DF) as a datum. Each PPO blends with diesel fuel with composition 50%-volume. As a result, PCO has higher BSFC (10%) before endurance test in comparison with diesel fuel, also PPaO (13%) and PJO (27%) show a similar condition. Surprisingly, all PPO have BSFC almost similar with DF after endurance test due to decreasing of engine components friction. On the other hand, PPO produces more uncompleted combustion than DF. Phosporus content has major responsibility of deposit growth. PCO, PPaO, and PJO result more engine deposits in comparison with DF, which accounts for 139,7%, 232,9%, and 288,9% respectively. Based on wear analysis, PCO has the best antiwear property among test fuels, whereas the worst is DF.